Optimization of Petroleum and Natural Gas Production—A Survey - Durrer, E. J.; Slater, G. E. (Management Science, 1977)
The paper surveys the literature dealing with the optimization of petroleum and natural gas production: Drilling, reservoir simulation, production planning and operations, enhanced recovery processes. Areas of possible future work are identified, such as optimal design and cost benefit studies of enhanced recovery projects. Problems are discussed which, in the authors' opinion, represent major obstacles in developing optimization models for production applications, for example, the nonlinearity and frequently large dimensions of the models, and the inherent uncertainties during the development phase of a field. Attention is also paid to the changing structure of the petroleum industry worldwide, which is shifting emphasis from traditional problems such as internal planning models to studies of new recovery processes, often labor-intensive and to be applied in small fields.